Multi-phase SPH modelling of air effect on the dynamic flooding of a damaged cabin. (15th February 2018) - Cao, X.Y.; Ming, F.R.; Zhang, A.M.; Tao, L.
Highlights: A multi-phase SPH model is developed and applied for studying the flooding of a damaged cabin. The velocity distribution of the air field in the flooding process is investigated. The effects of sizes and numbers of deck openings on flooding process are analyzed. Abstract: The air flow may take effects on the responses of the damaged ship in the dynamic flooding process. It not only relates to the amount of inflow but also the stability of the ship. In order to accurately predict the responses of a damaged ship, it is essential to take the air into account. In this study, a multi-phase SPH model combined with a dummy boundary method is proposed. One of the advantages of the new SPH model in solving this nonlinear problem is that, it does not rely on other algorithms to track the interface of different phases but can easily deal with breaking, splashing and mixing. The stability and accuracy of the numerical model are verified by comparing with experimental and published numerical results. The air captured in the flooding process is further studied with focus on the exchange of air and water near the opening. Finally, the effects of the sizes and number of the deck openings on the air flow are analyzed. It is found that the air flow can reduce the kinematic energy of inflow water, leading to decreases in the dynamic moment formed by the flooding water and sinking rate of damaged cabin.